Combination of DFT and Multitone Modulation in OFDM SystemsDOI: 10.14209/jcis.1994.3 - Cariolaro, G. Casimiro; Costanzi, A. (Journal of Communication and Information Systems, 2015)
In the implementation of OFDM systems one of the most consolidated schemes consists of an N-point DFT processor and an N-input N-output polyphase network, where N is the number of channels. Another recently developed scheme, which is attractive for its conceptual simplicity, consists of a polyphase filter, a multitone modulator (MTM) with carrier exp(j2Π(Fot)2/2N), and an equalizer. In this paper we derive a combination of the two previous schemes, where the number of channels Nis factored in the form N = M· I. The composite scheme consists of: 1) an l-point DFT processor; 2) a bank of I different MTM and 3) a bank of I different polyphase filters; and 4) a bank of I identical MTM with carriers. The composite scheme degenerates into the previous schemes in the extreme cases provided by factorization M I. Specifically, the DFT scheme is obtained with M = 1 and I = N, and the MTM scheme with M = N and I = 1. Here the attention is for the intermediate cases of factorization.